FIBER-OPTIC DISTRIBUTED SENSORS FOR EMERGING APPLICATIONS IN BIOMEDICAL DEVICES - Omarov, Orken (School of Engineering and Digital Sciences, 2023)
The concept of applying optical fiber sensors for 3-dimensional (3D) shape reconstruction purposes has become more popular in recent years. The literature review showcased various approaches to optical fiber based shape sensing and its applications. I developed a setup capable of estimating the shape of the needle in 3D space. The accuracy of the 3D shape reconstruction of the needle was acceptable. The results suggest that the main source of inconsistency is the ground truth data, as it was collected by hand. On the other hand, the reconstructed shape data were consistent among different trials and scenarios. The main source of error for the global shape reconstruction was the IMU sensor. The core of my work is experimental, meaning that the main goal was to implement the prototype and present proof of concept.
Keywords: type of access: restricted access; Fiber-optic distributed sensors; biomedical devices